Modelling the Desorption Isotherms of Chestnuts - Barroca, Maria João (2013)
The sorption isotherm of food material is pertinent in the processing and storage of food products. Desorption isotherms for peeled and unpeeled chestnuts were investigated using the hygrometric technique at 60 ºC and water activity (aw) ranged between 0.989 and 0.23. The experimental data were compared with four widely recommended models in the literature for food sorption isotherms (GAB, Freundlich, Henderson, and Smith). A non-linear least square regression program was used to evaluate the models constants. The four models were found to be acceptable for predicting the moisture sorption isotherms for chestnut cultivars. However, the empirical Smith model followed by the kinetic GAB was found to better represent the experimental data in the water activity range. Overall, the Smith model appears to be most suitable for fitting the desorption moisture isotherms data for the chestnut.